Letting the texts on RH speak for themselves (dis)continuity and (counter) point in CBCP statements - Francisco, Jose Mario C. (Philippine studies : historical and ethnographic viewpoints, 2015)
"In the fierce debate over any government legislation or program on reproductive health (RH), the Catholic Bishops' Conference of the Philippines (CBCP) represents the most vocal and consistent opposition from any institution in Philippine society. This article situates this opposition within the historical background of church involvement in social issues and offers a close reading of all its RH-related collective statements (1969-2014). Taking Catholic doctrine on marriage and family as given, it uncovers (a) shifting frames of reference in arguing the church's opposition, (b) ambiguity in its analysis of the state of Filipino families. These characteristics undermine the bishop's avowed task to provide effective pastoral guidance to Filipino Catholics."